Stakeholder capitalism, corporate governance and firm value - Franklin Allen; Elena Carletti; Robert Marquez (Goethe University Frankfurt, Center for Financial Studies (CFS), 2007)
We consider the advantages and disadvantages of stakeholder-oriented firms that are concerned with employees and suppliers as well as shareholders compared to shareholderoriented firms. Societies with stakeholder-oriented firms have higher prices, lower output, and can have greater firm value than shareholder-oriented societies. In some circumstances, firms may voluntarily choose to be stakeholder-oriented because this increases their value. Consumers that prefer to buy from stakeholder firms can also enforce a stakeholder society. With globalization entry by stakeholder firms is relatively more attractive than entry by shareholder firms for all societies.
urn:nbn:de:hebis:30-50972
Keywords: D02; D21; G34; L13; L21; 330; Firm Objective; Bankruptcy; Competition; Stakeholder Governance; Stakeholder; Shareholder Value; Vergleich; Corporate Governance; Unternehmenswert; Globalisierung; Wettbewerb; Theorie